Calorimetry Design, Theory and Applications in Porous Solids - Carlos Moreno-Piraján, Juan (IntechOpen, 2018)
Today, calorimetry is considered an art (although some consider it a tool) that studies the energy changes that occur during a change of state. This allows physicochemical analysis to study in detail the thermodynamic systems and to evaluate the different variables that establish the characteristics of the system itself. This book illustrates how the reader can use this technique in a wide spectrum of applications.